Molecular Basis of Redox Signaling - Franco, Maria Clara (2019)
Oxidants are produced in physiological and pathological conditions. The production of reactive nitrogen and oxygen species (RNS and ROS, respectively) can lead to vastly different cellular outcomes depending on their subcellular location, half-life, reactivity, gradients, and the antioxidant defenses. While oxidative stress caused by general oxidative damage is often nonspecific and linked to cell death by necrosis, at lower concentrations, ROS and RNS can act as second messengers regulating redox-sensitive signaling pathways, which elicit very specific cellular responses [1, 2]. Redox signaling is an intrinsic, tightly regulated component of cell metabolism, controlling cell growth, differentiation, and death. The interplay between the production of oxidants and the antioxidant defenses is highly regulated to maintain cellular redox homeostasis [3, 4]; thus, its dysregulation underlies many pathological conditions, including cancer, neurodegeneration, and cardiovascular and metabolic diseases. This special issue is focused on redox signaling in pathology and developments in redox-based therapies.